Mobile hotel reservations and customer behavior: channel familiarity and channel type - Kim, Jinkyung Jenny; Chua, Bee-Lia; Han, Heesup (SAGE Publications, 2021)
The present study is centered on mobile hotel reservations in the investigation of the interrelationships between value, attitude, satisfaction, and reuse intention in consideration of the moderating roles of the channel familiarity and the channel type. Utilizing a quantitative approach, the research hypotheses were tested using structural equation modeling and multiple-group analyses. The casual relationships proposed among the study variables were found to all be significant, and the importance of the utilitarian value was substantiated. Moreover, the analysis results denoted that the channel familiarity is an important moderator that affects the strength of the relationships between (1) the attitude and the reuse intention and (2) satisfaction and the reuse intention, which suggests that a different approach should be arranged for novice and expert users. Also, channel type moderated the links between (1) hedonic value and satisfaction, (2) utilitarian value and satisfaction, (3) attitude and the reuse intention, and (4) satisfaction and the reuse intention, which separately provided more relevant implications for the hotel owned and the third-party owned channels.